b) x(x-4) - 2x+8 = 0
x(x-4) - 2(x-4) = 0
(x-2) (x-4) = 0
TH1: x-2=0 TH2: x-4=0
x=2 x=4
Vậy x\(\in\){2;4}
\(b,\Leftrightarrow\left(x-4\right)\left(x-2\right)=0\Leftrightarrow\left[{}\begin{matrix}x=2\\x=4\end{matrix}\right.\\ c,\Leftrightarrow\left(x-5\right)\left(x+5\right)-\left(x+5\right)=0\\ \Leftrightarrow\left(x+5\right)\left(x-6\right)=0\Leftrightarrow\left[{}\begin{matrix}x=6\\x=-5\end{matrix}\right.\\ d,\Leftrightarrow\left(2x-1\right)^2-\left(2x-1\right)\left(2x+1\right)=0\\ \Leftrightarrow\left(2x-1\right)\left(2x-1-2x-1\right)=0\\ \Leftrightarrow x=\dfrac{1}{2}\\ e,\Leftrightarrow\left(3x-1-x-5\right)\left(3x-1+x+5\right)=0\\ \Leftrightarrow\left(2x-6\right)\left(4x+4\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=-1\\x=3\end{matrix}\right.\\ f,\Leftrightarrow\left(x-2\right)\left(x^2+2x+4\right)-\left(x-2\right)\left(x-12\right)=0\\ \Leftrightarrow\left(x-2\right)\left(x^2+x+16\right)=0\\ \Leftrightarrow\left[{}\begin{matrix}x=2\\\left(x+\dfrac{1}{2}\right)^2+\dfrac{63}{4}=0\left(vô.n_0\right)\end{matrix}\right.\\ \Leftrightarrow x=2\)
b) x(x-4)-2x+8=0
x(x-4)-2(x-4)=0
(x-4)(x-2)=0
th1: x-4=0
x=4
th2: x-2=0
x=2
Vậy x thuộc tập hợp 4;-2
c) x2-25-(x+5)=0
x2-52-(x+5)=0
(x-5)(x+5)-(x+5)=0
(x+5)(x-5-1)=0
TH1: x+5=0 Th2: x-5-1=0
x=-5 x= 6
Vậy x\(\in\){-5;6}
d) (2x-1)2-(4x2-1)=0
(4x2-4x+1)-(4x2-1)=0
4x2-4x+1-4x2+1=0
(4x2-4x2)+(1+1)-4x=0
0+2-4x=0
4x=2
x=1/2
e) (3x-1)2-(x+5)2=0
(3x-1-x-5)(3x-1+x+5)=0
(2x-6)(4x+4)=0
TH1: 2x-6=0 TH2: 4x+4=0
x=3 x=-1
Vậy x\(\in\){-1;3}
f) x3-8-(x-2)(x-12)=0
x3-23-(x-2)(x-12)=0
(x-2)(x2+2x+4)-(x-2)(x-12)=0
(x-2)(x2+2x+4-x+12)=0
(x-2)(x2+x+16)=0
TH1: x-2=0 TH2: x2+x+16=0
x=2 x2+x=-16
x= vô lí (x2>2\(\Rightarrow\)x\(\notin\)số âm)
Vậy x=2